Emotional regulation as a mediator between the filial behaviour of the oldest son and subjective well‐being of older parents in Pakistan. Issue 1 (23rd April 2019) - Hassan, Sumara Masood Ul; Hamid, Tengku Aizan; Haron, Sharifah Azizah; Ibrahim, Rahimah
Abstract : Background: The link between the filial behaviour of an adult child and older parents' well‐being is well entrenched, and theoretical evidence has indicated that it may be mediated by emotional regulation. Therefore, the current study aimed to examine whether emotional regulation (i.e. cognitive reappraisal and suppression) mediates the association between filial behaviour of the oldest son (i.e. the filial behaviour of respect and filial behaviour of daily maintenance) and subjective well‐being in older parents. Methods: This correlational study recruited 400 community‐dwelling older parents in Rawalpindi Pakistan through a multistage cluster random sampling technique. Subjective well‐being was measured by Concise Measure of Subjective Well‐being; filial behaviour was examined through receipt of 12 domains; emotional regulation was assessed by using the Emotional Regulation Questionnaire. The structural equation modelling was employed to test the mediation effects. Results: Cognitive reappraisal was found to partially mediate the relationship between filial behaviour of respect and subjective well‐being (β in direct model = 0.661, P < 0.000; β in full mediational model = 0.327, P < 0.000), but it failed to mediate between filial behaviour of daily maintenance and subjective well‐being (β in direct model = 0.080, P = 0.149; β in full mediational model = 0.030, P = 0.362). Moreover, suppression did not exert mediation effects in the associations between the filial behaviour of respect and subjective well‐being (β = 0.003, P = 0.338); and filial behaviour of daily maintenance and subjective well‐being (β = −0.004, P = 0.221). Conclusions: Taken together, the results suggest that different dimensions of the filial behaviour of the oldest son exert differential effects on emotional regulation and subjective well‐being in older parents. Based on the current findings, there is a need to develop adaptive emotional regulatory capacity intervention programs for the development and enhancement of subjective well‐being in older parents within their familial context.